2023
DOI: 10.1027/0269-8803/a000309
|View full text |Cite
|
Sign up to set email alerts
|

Avoidant Personality Disorder Symptoms and Cardiovascular Reactivity to Psychological Stress Tasks With Increasing Cognitive Demands

Abstract: Abstract. This study aimed to investigate whether and how avoidant personality disorder symptoms are related to cardiovascular reactivity to stress tasks with different levels of cognitive demands. The revised Chinese edition of the avoidant personality disorder subscale of Personality Diagnosed Questionnaire-4+ (PDQ-4+) was administered to 222 undergraduate students randomly assigned to psychological stress tasks (i.e., mental arithmetic tasks) with low, moderate, or high cognitive demands (manipulated by tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…With respect to physiological responses to social evaluative stress, we observed that individuals with high-trait Detachment and Negative Affect had a more blunted heart rate reactivity compared to the low-trait group. This was as expected, given that previous research also found this relationship in individuals with CPD (Deckers et al, 2015;Hu et al, 2022). Blunted reactivity to psychosocial stressors is suggested to reflect deficits in the fronto-limbic pathway in the brain, which results in dysregulation of motivation and behavior (Carroll et al, 2017;Ginty et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…With respect to physiological responses to social evaluative stress, we observed that individuals with high-trait Detachment and Negative Affect had a more blunted heart rate reactivity compared to the low-trait group. This was as expected, given that previous research also found this relationship in individuals with CPD (Deckers et al, 2015;Hu et al, 2022). Blunted reactivity to psychosocial stressors is suggested to reflect deficits in the fronto-limbic pathway in the brain, which results in dysregulation of motivation and behavior (Carroll et al, 2017;Ginty et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
“…Although two of these studies showed exaggerated emotional reactivity to stress in individuals with CPD compared to a control group (Aleknaviciute et al, 2016;Deckers et al, 2015), results concerning physiological outcomes have been contradictory. On the one hand, blunted physiological reactivity in response to stress has been observed in individuals with CPD (Deckers et al, 2015;Hu et al, 2022). On the other hand, the study of Aleknaviciute et al (2016) showed stronger physiological reactivity in CPD individuals in response to stress compared to individuals with Borderline personality disorder (a Cluster B PD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation